THEORETICAL APPROACHES TO INNOVATION MANAGEMENT: COMPARATIVE ANALYSIS AND INTEGRATION OF MODELS - Ажаман, Ірина А.; Сливка, Дмитро О. (Journal of Strategic Economic Research, 2025)
The article examines modern theoretical approaches to innovation management as a key factor in ensuring the competitiveness and sustainable development of enterprises in the context of the knowledge economy, rapid technological renewal and increased global competition. The constant growth of the complexity of the economic environment, the increasing role of technological, economic and social interconnections necessitate the creation of new integrative models of innovation management that can effectively combine internal resources and external capabilities of enterprises, ensuring their flexibility and adaptability. A comprehensive analysis of the main theoretical approaches to innovation management is carried out, including evolutionary, systemic, functional, process, strategic, resource, marketing, synergistic and network. Each of these approaches is considered from the standpoint of its essence, strengths, limitations, and areas of appropriate application. In particular, the evolutionary approach, based on Schumpeter's ideas of creative destruction, focuses on the dynamic development of innovations through variation and selection, while the systemic approach offers a vision of the enterprise as an integral open system with interconnected subsystems, integrating innovations into the overall management structure. Functional and process approaches ensure the detailing of innovation tasks and the sequence of their implementation, which allows to improve the quality of management and the efficiency of innovation. The strategic approach emphasizes the importance of innovations as a tool for achieving long-term competitive advantages, while the resource approach focuses on the optimal use of material, financial, human and information resources. The marketing approach is aimed at ensuring the market orientation of innovations through a deep understanding of consumer needs and behavior, while the synergistic and network approaches emphasize the importance of nonlinearity, self-organization and cooperation between different participants in innovation processes, forming modern innovation ecosystems and open innovation networks. Particular attention is paid to the need to integrate these approaches, which is explained by the complexity and multifactorial nature of innovation activities, as well as the requirements of digitalization, globalization and the development of open innovation. The advantages and disadvantages of these approaches are summarized in a comparative table, which allows us to conclude that an integrated approach to innovation management is important. It is emphasized that the integration of various theoretical models makes it possible to adapt the innovation policy of enterprises to specific conditions of activity, to take into account the specifics of the industry, the level of innovation potential and the stage of the organization's life cycle. This helps to increase the efficiency of management decisions, reduce risks, create a favorable innovation environment and ensure sustainable development in a dynamic and competitive knowledge economy. Because of the study, the scientific and practical significance of the systematization and comparative analysis of theoretical approaches that form the methodological basis of modern innovation management has been confirmed. This creates preconditions for the further development of integrative management models that meet the challenges of digital transformation, increased global competition, and the needs of high-tech and knowledge-intensive industries.